The invasive fish tapeworm Atractolytocestus huronensis (Cestoda), a parasite of carp, colonises Africa - Scholz, Tomáš; Tavakol, Sareh; Halajian, Ali; Luus-Powell, Wilmien J (Parasitology research, 2015)
Biological invasions represent a serious threat for aquaculture because many of introduced parasites may negatively affect the health state of feral and cultured fish. In the present account, the invasive tapeworm Atractolytocestus huronensis Anthony, 1958 (Cestoda: Caryophyllidea), which was originally described from North America and has been introduced to Europe including the British Isles with its specific host, common carp (Cyprinus carpio L.), is reported from Africa for the first time. Its recent introduction to South Africa, where it was found in four localities where common carp is cultured, is another evidence of insufficient prophylactic measures and inadequate veterinary control during transfers of cultured fish, especially common carp, between continents. Together with the Asian fish tapeworm, Bothriocephalus acheilognathi, A. huronensis is another fish tapeworm with ability to spread throughout the globe as a result of man-made introductions of its fish hosts.
Keywords: Fish Diseases; nemoci ryb; Carps; Introduced Species; cestodózy; kapři; Cestoda; Cestode Infections; Africa; Geography; zeměpis; Animals; Afrika; zvířata; zavlečené druhy